Climb, koala! - Szymanski, Jennifer (Washington, DC : National Geographic, 2017)
Presents information about koalas, including characteristics, basic behavior, and habitats.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Ages 2 to 5.
Pre-school.
Description based on print version record.
Keywords: Koala -- Juvenile literature; Koala; JUVENILE NONFICTION -- Animals -- Mammals; JUVENILE NONFICTION -- Reader -- Beginner; Koala; Electronic books- OSLIS; Readers (Publications); Juvenile works; Readers (Publications); Readers (Primary).; Nonfiction; Electronic books